Correction to: Report from the 2nd Cardiovascular Outcome Trial (CVOT) Summit of the Diabetes and Cardiovascular Disease (D&CVD) EASD Study Group - Schnell, Oliver; Standl, Eberhard; Catrinoiu, Doina; Genovese, Stefano; Lalic, Nebojsa; Skra, Jan; Valensi, Paul; Rahelic, Dario; Ceriello, Antonio (Cardiovascular diabetology, 2017)
Following publication of the original article [1], author Antonio Ceriello requested that a correction be published in relation to his affiliations. His correct affiliations have been updated in this erratum. This correction is very important for the correct assignment of funds to his Institutions.